Radnice Brno – Sever - Stehlík, Michal (Vysoké učení technické v Brně. Fakulta architektury)
Nová radnice pro městskou část Brno sever. Centrálně umístěná solitérní budova radnice v parku se smíšeným využitím. Radnice, knihovna, art center s komerčním parterem.

New town hall for the district of Brno-Brno sever. Central soliter position of mixed use building in green public space. Town hall, library, art center and commercion in ground floor
New town hall for the district Brno-North
Keywords: radnice; Brno sever; kasárny Černá Pole; architektura; urbanismus; Provazníkova; Bieblova; tř. Generála Píky; diplomová práce; vut brno; centrální ring; kruhová stavba; knihovna; art center; NEW TOWN HALL FOR THE DISTRICT BRNO-NORTH; Brno sever; barracks černá Pole; architecture; urbanism; Provazníkova; Bieblova; tř. Generála Píky; master thesis; central ring; vut brno; library; art center; central building; round building